Pemanfaatan Mobile JKN Sebagai Bentuk Digitalisasi Kesehatan Untuk Meningkatkan Efektivitas Layanan Kesehatan - Nursuciyani Jamal; Andi Sri Adinda (Lembaga Pengembangan Kinerja Dosen, 2025)
The National Health Insurance program (JKN) has been in effect in Indonesia since early 2014, administered by the Social Security Administration (BPJS). The purpose of this community service program is to enhance the role of youth in optimizing the use of Mobile JKN and to assist the community in utilizing it. Mobile JKN is an innovation for the community, eliminating the need to wait in long queues at healthcare services. The participants were adolescents, specifically 13 students from MTs. Muhammadiyah Palleko in Takalar Regency. The method used was to provide outreach through presentations on the procedures for using Mobile JKN, followed by discussions to clarify any issues that the students still lacked. The results of this community service program are expected to increase the youth's knowledge of the use and utilization of Mobile JKN as a form of digital health care that can improve the effectiveness of healthcare services, enabling them to become agents of change in the success of the JKN program in Takalar City.